Oltre le specificità di genere. Cura e diritti nella prospettiva relazionale di Amartya Sen e Martha Nussbaum - Erasmo, Valentina (SocietàMutamentoPolitica, 2021)
At the thresholds of 2020, gender differences are still reason of inequalities, even in the most economically advanced countries, as shown by the Global Gender Gap Report. Indeed, democratic and liberal societies are dominated by behavioural ‘masculine’ dynamics, according to homo economicus’ paradigm. Many representatives of feminism, as Ortner, complain the strong competitiveness of homo economicus for representing individual decisions, where are lost those horizons not regulated by markets laws: one of these is caregiving, understood as health and/or home care, where female figures prevail. I would suggest an alternative to these perspectives, androcentric and feminist, which enables to go beyond gender specificity. I have proceeded with Sen’s anthropological proposal where man is ‘relation’ with himself herself, into intrapersonal space, and with the others, into interpersonal space. Thanks to ‘multiple identities’, we can rediscover the value of reciprocity in social interactions, culminated in the birth of relational goods which returns the importance of care in these interactions which increase social capital, as in caregiving. Since the creation of relational goods two questions arise: on the one hand, asking if this may become the starting point for an expansion of care’s reciprocity from the intersubjective domain to their reference community; on the other, discussing whether an ethics of care may coexist with an ethics of rights. The answer is affirmative for both, but it requires the overcoming of gender’s dichotomy, where the ethics of care is declined with a female voice, as compassion, and the ethics of rights with a male voice, as rationality. A choral answer is required, able to harmonise, without confusing, the level of care with the respect of rights, like the goals-rights system of Sen in dialogue with the ethics of care of Nussbaum, careful to the most human aspects of the existence.